Estudio comparativo entre altura de fondo uterino y fecha de última menstruación, y su relación con la edad gestacional por Capurro en mujeres gestantes a término que paren en el Hospital Isidro Ayora. - Espinosa Armijos, Jorge Leonardo (2013)
The knowledge of gestational age is an important factor in the management of pregnancy, it is crucial in clinical decision making, the date of the last menstrual period is the primary reference that we used to calculate gestational age, and in the absence of this, fundus height allows approximate correlation, however the margin of error in this measurement is large. This article is based on a comparative study between fundus height (AFU), date of last menstrual period (LMP), and their relationship with physical examination in the newborn Capurro, conducted in patients with term pregnancies in the area of obstetrics and gynecology at the Hospital Isidro Ayóra. 113 medical records were reviewed, there was LMP, AFU by the method of McDonald, and review of Capurro. Most births occurred between 39 and 40 weeks. Highest correlation was found between date of last menstrual period and Capurro, the height of uterine fundus less accurate indicator for predicting gestational age. So the margin of error for LMP was ± 4 days, and to AFU was 1 week 3 days.